BENTUK UNGKAPAN KOMPLEKS DALAM KUMPULAN PUISI âWEKWEKWEKâ KARYA MUSTOFA BISRI DITINJAU DARI SEGI HUBUNGAN PARADIGMATIK - Dalman, Dalman (JURNAL PESONA, 2018)
AbstractThe research has been conducted with the aim of analyzing complex expressions in the poem "Wekwekwek" in terms of paradigmatic relationships. This study used descriptive qualitative method. The paradigmatic relationship is a correlation between the morphemes or the alternating words in one such poem structure and has the same function. Paradigmatic relationships in complex phrases which can be seen by using linguistic tools of inflection, auxiliary words, word order, and comparative form. To understand the intentions conveyed by poet in poetry "Wekwekwek" by Mustofa Bisri can be known through paradigmatic relationship. Thus, in order to understand the intent and message the poet wishes to convey in his poetry, we can interpret the complex form of the poem by the paradigmatic relation.Key Words: Complex Expression Form, Paradigmatic Relationships, PoetryÂ